THE DESIGN OF FISHING BOATS MADE BY FIBERGLASS - Rama Agus Mulyadi; Aprilia Syah Putri; Dona Setya; Hamidi Hamidi (Universitas Teuku Umar, 2021)
As a means of transportation in the process of catching fish, ship must be owned by fishermen. The purpose of this study was to determine the durability of ship made of fiberglass material and to know when the ship run and stopped. This research was conducted for 4 months in a fishing laboratory assisted by 2 lecturers and 3 students. Students were involved in order to gain knowledge and experience in making boats made of fiberglass. With an experimental methods, data collection was done by direct observation of the design process, material testing, durability, and stability of the ship at sea. The results of this research were obtained in terms of making boats, in which it had a quite long stage starting from knowing the place where the boat was used, designing, making, and testing it in the manufacture. Thus, it is necessary to be careful during the work in order to get better results. Based on the endurance and leak tests, the boat had good resistance and did not leak, so it could be further developed.